How to promote the hierarchical diagnosis and treatment system: A tripartite evolutionary game theory perspective - Tao, Chunhai; Chen, Xi; Zheng, Wenji; Zhang, Zehao; Tao, Ruoyan; Deng, Rui; Xiong, Qizhe (Frontiers in Psychology, 2023)
Due to the disorderly access to medical care and inefficient use of health resources, scholars have been driven to focus on the advancement of the hierarchical diagnosis and treatment in the circumstance of the growing demand for promoting health system reform. Hence, we have prospect theory integrated into a tripartite stochastic evolutionary game model of the local government health departments, the medical institutions and the patients in the system promotion of the hierarchical diagnosis and treatment. The simulation shows the specific influencing mechanism of the psychological perceived value and loss avoidance of game subjects. Meanwhile, the system promotion under different medical cultures has also been discussed. The results indicate that: 1) The amount and duration of financial subsidies of local government health departments for the other two parties are the key factors influencing the system’s evolution. Participating in the establishment of the hierarchical diagnosis and treatment system is beneficial to resource optimization and long-term development for medical institutions. For patients, compared to the cost of treatment, recovery rate is the more significant factor in the system; 2) The convergence of the game system to the equilibrium point will be accelerated by the increase of the risk sensitivity coefficient. The promotion of the hierarchical diagnosis and treatment system can be promoted with the perfection of the financial investment in medical treatment by local government health departments. The convergence point of the system cannot be changed by the loss avoidance factor, but the speed of evolution will be significantly slowed down with the increase of the loss avoidance factor; 3) The simulations demonstrate that the intensity coefficient of stochastic disturbance has an impact on the speed of decision-making evolution of participating in system promotion. In detail, it has been concluded that with the health departments’ intervention, patients under rural medical culture are more inclined to be cooperators than patients under urban or town medical culture.